Kota Kupang sebagai Laboratorium Desentralisasi: Analisis Yuridis Otonomi Daerah dalam Reformasi Hukum Indonesia - Theresia Irnatesa Vivin; Sanctissima Trinitas Gute Kothen; Destriani Silla; Elisabeth Rari Basa; Rehan Glen Ly (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Regional autonomy in Kupang City still faces several structural obstacles, particularly the imbalance between the principle of decentralization and the financial and bureaucratic capacity at the local level. This study aims to evaluate how legal norms regarding regional autonomy are implemented and the obstacles that impact the success of decentralization within the legal reform process in Indonesia. This study employs a legal-normative approach using a literature review method, specifically by analyzing legislation, local regulations, and relevant academic literature. The analysis is conducted qualitatively through legal interpretation and the harmonization of applicable regulations. The results of the normative research indicate that the implementation of regional autonomy in Kupang City remains limited due to high dependence on funds allocated by the central government, the existence of an overly formal bureaucratic culture, and a lack of alignment between regulations from the central government and local governments. These conditions have led to the phenomenon of “pseudo-autonomy,” which hinders the achievement of responsive and transparent local government administration.